BEBAN YANG DIRASAKAN OLEH PENDERITA TB MDR DAN KELUARGA: REVIEW LITERATUR KUALITATIF - Sulistyono, R Endro; Tristiana, Rr Dian (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2018)
Background: The incidence of Multiple Drugs Resistance Tuberculosis (TB MDR) is still very high. TB MDR treatments requires a long period care that could lead to an impact on TB MDR patients and their families. This study aims to explore the perceived burden of TB MDR patients and their families. Method: Review literature was conducted through a search of four journal databases which later found 8 articles according to the inclusion criteria which were then identified, evaluated and synthesized. Results: The literature review found four major themes related to the perceived burden by TB MDR patients and their family, namely; physical, psychological, social and financial burden. Discussion: various problems arise due to the illness suffered by MDR TB patients and families. Understanding the difficulties and burdens experienced by MDR TB patients and their families is important in order to be able to intervene according to the problems that might arise due to MDR TB disease. Conclusion: The government needs to provide social protection to patients with MDR TB and families. Health professional workers need to add physical and psychological interventions to relieve the burden felt by MDR TB patients and their families. Keywords: Multiple Drugs Resistance Tuberculosis; Perceived burden; Sufferers; family; literature review